Global Conservative Solutions of a Generalized Two-Component Camassa-Holm System - Feng Zhang; Han Yang; Yonghong Wu (Journal of Applied Mathematics)
The Cauchy problem for a generalized two-component Camassa-Holm system is investigated. Following the idea of fixed points and using new sets of independent and dependent variables, the existence of the global conservative solutions for the system is established.